Notes on Australian species of Salsola (Chenopodiaceae) and validation of Salsola sabrinae, nom. et stat. nov. - Mosyakin, S.L. (Український ботанічний журнал, 2018)
Taxonomic opinions on Australian taxa of Salsola sensu stricto (Chenopodiaceae) are analyzed in a historical context. It is
concluded, based on available evidence, that the genus is probably represented in Australia and adjacent regions of southeasternmost
Asia by several (4–5 or more) native species, including the currently recognized S. australis R. Br. (also naturalized in southwestern
North America and southern Africa) and supposedly related taxa (S. macrophylla R. Br., S. brachypteris Moq., S. australis var.
strobilifera (Benth.) Domin, etc.); the presence of introduced Eurasian species cannot be excluded as well. The new name Salsola
sabrinae Mosyakin is proposed for the native Australian taxon originally described as S. tragus L. subsp. grandiflora S. Rilke (non
S. grandiflora Link ex Steud.) and reported mainly from northern tropical and subtropical regions of Australia (northern Western
Australia, Northern Territory, and Queensland). It is emphasized that further dedicated morphological, molecular phylogenetic,
and phylogeographic studies are needed, in comparison with Eurasian species, for achieving a reliable taxonomic scheme for
Australian/Australasian species of Salsola and for clarifying issues of their immigration to and diversification in Australia. В історичному контексті проаналізовані таксономічні погляди на австралійські таксони роду Salsola sensu stricto (Chenopodiaceae). На підставі наявних свідчень зроблено висновок про те, що цей рід, ймовірно, представлений в Австралії та прилеглих районах південно-східної Азії кількома (4–5 або більше) аборигенними видами, включаючи нині визнаний вид S. australis R. Br. (також натуралізований у південно-західній частині Північної Америки та Південній Африці) і, ймовірно, споріднені з ним таксони (S. macrophylla R. Br., S. brachypteris Moq., S. australis var. strobilifera (Benth.) Domin та інші); наявність адвентивних євразійських видів також не виключена. Нова назва Salsola sabrinae Mosyakin запропонована для австралійського таксона, який був раніше описаний як S. tragus L. subsp. grandiflora S. Rilke (non S. grandiflora Link ex Steud.) і наводиться переважно для північних тропічних і субтропічних регіонів Австралії (північна частина Західної Австралії, Північна Територія та Квінсленд). Зазначено, що для розробки надійної таксономічної схеми для австралійських / австралазійських видів Salsola та для з'ясування питань їхньої міграції до Австралії та подальшої диверсифікації на цій території необхідні додаткові спеціальні морфологічні, молекулярно-філогенетичні та філогеографічні дослідження. В историческом контексте проанализированы таксономические взгляды на австралийские таксоны рода Salsola sensu stricto (Chenopodiaceae). На основании имеющихся свидетельств, сделан вывод о том, что этот род, вероятно, представлен в Австралии и прилегающих районах Юго-Восточной Азии несколькими (4–5 или более) аборигенными видами, включая ныне признанный вид S. australis R. Br. (также натурализованный в юго-западной части Северной Америки и в Южной Африке) и, очевидно, родственные таксоны (S. macrophylla R. Br., S. brachypteris Moq., S. australis var. strobilifera (Benth.) Domin и другие); наличие адвентивных евразийских видов также не исключено. Новое название Salsola sabrinae Mosyakin предложено для австралийского таксона, который был ранее описан как S. tragus L. subsp. grandiflora S. Rilke (non S. grandiflora Link ex Steud.) и приводится в основном для северных тропических и субтропических регионов Австралии (северная часть Западной Австралии, Северная Территория и Квинсленд). Отмечено, что для разработки надежной таксономической схемы для австралийских / австралазийских видов Salsola и для прояснения вопросов их миграции в Австралию и дальнейшей диверсификации на этой территории необходимы дополнительные специальные морфологические, молекулярно-филогенетические и филогеографические исследования.